The Importance of Deductions in Response to the Personal Income Tax: Bunching Evidence from Germany - Simeon Schächtele (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
For its promise to summarize all necessary information to calculate efficiency losses from taxation (Feldstein, 1999), the elasticity of taxable income (ETI) has become one of the most widely studied parameters in public economics. More recently, Chetty (2009) and others have pointed out the limits of the sufficiency property of the ETI and reemphasized the importance of separating the behavioral margins along which taxpayers react. Using German tax administration data from 2007, this paper documents bunching patterns that are consistent with deduction behavior playing a key role in response to the personal income tax. Because the set of available deductions and the strength of enforcing their proper use are policy choices, this result cautions against construing the ETI as a structural parameter that determines optimal tax rates independently of non-tax rate policy instruments. For reference, I also report estimates for the local ETI at the personal allowance threshold from applying Saez' (2010) bunching estimator.
Keywords: H24; H26; H21; 330